Personality and endogenous/major depression: an empirical approach to typus melancholicus: 1. Theoretical issues - Stanghellini, Giovanni; Mundt, Christoph (Psychopathology, 1997)
The concept of typus melancholicus (TM) was shaped by Tellenbach by means of phenomenological analysis in order to describe the premorbid and intermorbid personality of endogenous depressives. In this paper, the authors delineate the core properties of TM - i.e. orderliness, conscientiousness, norm orientation and intolerance of ambiguity - as a point of departure for empirical-statistical research. Qualitative and quantitative studies inquiring the characteristics of TM are reviewed in order to point out its well-established personality dimensions. Alternating methodological steps are proposed, combining phenomenological hypotheses with empirical-statistical tests (hermeneutic complementarity) in order to validate and differentiate the TM concept. The question whether TM should be considered as a personality disorder and the ethical attitude of subsiding appreciation of the TM in different generations of psychiatrists are discussed. It is emphasized that the TM concept brings otherwise unsystematized observations of depressives; intermorbid personality features into a coherent theoretical framework.